The reasons why cardiologists should consider prematurity at birth and intrauterine growth retardation among risk factors. Issue 5 (May 2016) - Bassareo, Pier P.; Marras, Andrea R.; Cugusi, Lucia; Zedda, Angela M.; Mercuro, Giuseppe
Abstract : The survival percentage of infants born preterm has risen steadily worldwide thanks to the giant steps forward made in the field of perinatal (the period immediately after birth) and neonatal (the first 4 weeks of birth following delivery) medicine. However, prematurity at birth and consequent low birth weight still represent the major causes of neonatal morbidity and mortality. Infants born preterm are at high risk of developing neurological, ophthalmological, and gastrointestinal complications as well. Furthermore, extensive more recent epidemiological findings have demonstrated an increase in risk factors and a higher mortality rate due to cardiovascular causes in patients born preterm and/or with intrauterine growth restriction. The aim of this review is to provide scientific evidence about how the cardiovascular system may be negatively influenced by prematurity and by a low birth weight that should by rights be viewed as new cardiovascular risk factors. This condition is referred to as 'cardiovascular perinatal programming'. In the light of the above, an early, constant, and prolonged cardiovascular follow-up should be implemented in former preterm individuals.